Analysis of Jurisprudential Arguments for Entrepreneurship from the Perspective of Imamiyyah jurisprudence - Sadeghi Bi-Abari, Mohammad Sadegh; Rezaei, Mohammad; Pilehvar, Marzieh (Legal Studies in Digital Age, 2025)
Entrepreneurship occupies a prominent position in the Islamic economic system and in the conduct of the Infallible Imams, being regarded as one of the essential elements of human and social life. The Qur’an portrays humanity, through examples of predecessors, as inherently entrepreneurial—a trait that serves as a foundation for generating wealth, alleviating unemployment and idleness, and fulfilling the needs of societies. In Islam, entrepreneurship is recognized not merely as material profit-seeking but as a religious obligation whose ultimate aim is achieving falah (prosperity) and human happiness, thereby realizing a hayat tayyibah (goodly life). This study analyzes the jurisprudential foundations of entrepreneurship from the perspective of Imamiyyah jurisprudence, examining its role in ensuring economic independence, alleviating poverty and deprivation, and satisfying human needs while preserving dignity and freedom. The findings indicate that Imamiyyah jurisprudence conceptualizes entrepreneurship as having wide-ranging effects on various dimensions of human life—including personal, financial and economic, social, scientific, and political aspects. Accordingly, entrepreneurship is not only considered a driver of dynamism and a means of meeting societal needs but also as a tool for attaining human perfection and happiness within the divine order. This article particularly emphasizes the importance of entrepreneurship in realizing a hayat tayyibah and demonstrates that, within the framework of Imamiyyah jurisprudence, entrepreneurship constitutes an essential path toward achieving welfare, social justice, and spiritual growth.